Evaluation of potent Trichoderma strains against anthracnose-twister disease and enhancement of crop health and bulb yield in kharif onion - Dutta, Ram; Jayalakshmi, K.; Kumar, Satish; Soumia, P. S.; Auji, Radhakrishna; Mahajan, Vijay; Singh, Major (Frontiers in Sustainable Food Systems, 2025)
In India, the productivity of onions during the kharif season (June-October) is quite low compared to the Rabi season (December-April). The yield losses in kharif onion are primarily attributed to the increased incidence of anthracnose-twister disease, which is often exacerbated by concurrent monsoon rains and high relative humidity during the kharif. To address this issue, a field study was conducted over three consecutive years (2021–2023) to assess the performance of eleven different Trichoderma strains in managing anthracnose-twister disease and improving plant growth and bulb yield in kharif onion. The strains were initially selected based on their ability to inhibit the growth of the anthracnose pathogen Colletotrichum gloeosporioides (in vitro confrontation assay) and HCN production; amylase, and protease production. The selected strains were also screened in vitro for PGPA traits (IAA and siderophore production; ability to grow in N2 free media, PO42-, Zn, and K solubilization). The antagonistic activity of Trichoderma strains against C. gloeosporioides ranged from 18.8% to 70.0% with T. longibrachiatum (OGRDT2) recording the highest inhibition (70%). Application of GRDT2 and OGRDT2 reduced the PDI to 36.00 ± 0.98 and 37.06 ± 1.38, respectively, compared to 62.77 ± 0.14 in the untreated control. The T. longibrachiatum (OGRDT2) and T. harzianum (GRDT2) treated plots registered an increased plant height (54.97 ± 0.80 and 53.29 ± 0.79 cm) and pseudostem diameter (13.96 ± 0.18 and 13.76 ± 0.20mm) compared to the control (42.68 ± 1.90 and 10.55 ± 0.04 mm), respectively, under field conditions. Additionally, these treatments supported higher biomass, as reflected in the increased normalized dry weights of the shoot (10.82 ± 0.89% and 10.39 ± 1.76 %), root (12.27 ± 0.11 % and 11.86 ± 2.67 %), and bulb (12.90 ± 0.65 % and 12.21 ± 0.81 %). The chlorophyll contents were again higher (4.1 ± 1.44 and 4.1 ± 0.83 mg/ml) in OGRDT2 and GRDT2 treated plants than 3.3 ± 0.80 mg/ml in the untreated control. The GRDT2 and OGRDT2 treated plots supported higher bulb yield of 20.66 ± 1.42 t/ha and 19.21 ± 0.87 t/ha compared to control (16.52 ± 0.69 t/ha). Our study demonstrated that T. harzianum (GRDT2) and T. longibrachiatum (OGRDT2) effectively reduced anthracnose severity and therefore can be explored for management of Anthracnose-twister disease of onion.